2019
DOI: 10.1002/jcp.28020
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in osteoarthritis: Novel spotlight

Abstract: Osteoarthritis (OA) is the most common type of arthritis and no longer is considered as an absolute consequence of joint mechanical use (wear and tear); rather recent data demonstrate the pivotal role of inflammatory mediators in the development and progression of this disease. This multifactorial disease results from several environmental and inherited factors. Genetic cannot solely explain all the contribution share of inheritance and, this way, it is speculated that epigenetics can play a role, too. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 150 publications
0
31
0
1
Order By: Relevance
“…MiRNA has been widely investigated for their role in gene regulation; by binding to mRNA 3′-UTRs, miRNA can affect many protein-encoding genes at the post-transcriptional levels [22,24,57]. It is proved that some miRNA are differentially expressed in OA cartilage samples with respect to normal ones, demonstrating their role in the development and progression of OA [23,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA has been widely investigated for their role in gene regulation; by binding to mRNA 3′-UTRs, miRNA can affect many protein-encoding genes at the post-transcriptional levels [22,24,57]. It is proved that some miRNA are differentially expressed in OA cartilage samples with respect to normal ones, demonstrating their role in the development and progression of OA [23,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…(b) development and remodeling that entail orderly transitions from stem cell proliferation to differentiation; (c) phenotypic variation that results from changes in the timing of developmental transitions, or heterochrony; (d) adaptation that can arise quite rapidly; and (e) an "environmental sensitivity" and adaptability of this complex system that is mediated by epigenetic modification of gene networks, rather than by gene mutations or constant evolution of entirely new signaling pathways over geological time. This last point has been illustrated by various studies (Fathollahi, Aslani, Jamshidi, & Mahmoudi, 2019;Reppe, Datta, & Gautvik, 2017;Van Meurs, Boer, Lopez-Delgado, & Riancho, 2019;Vrtacnik, Mare, & Ostanek, 2014).…”
mentioning
confidence: 80%
“…Recently, it has been reported that OA is not the absolute consequence of joint mechanical use. The implication of inflammatory cytokines contributes to the development and progression of OA 10. Cartilage, subchondral bone, and synovium probably have critical roles in OA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modification has been involved in OA pathogenesis at all of its levels, including DNA methylation, histone modification, miRNAs, and long non-coding RNA 10. Accumulating evidence has demonstrated that miRNAs play a crucial role as regulators of cartilage biology and in OA pathogenesis 14.…”
Section: Introductionmentioning
confidence: 99%